A low-VOC, low-odor biodegradable material and its preparation method and application

By adding specific components and process to the biodegradable materials, the problem of heavy odor in the material is solved, the effect of low VOC and low odor is achieved, and the material's aging resistance is improved, and its application in the field of membrane bags is expanded.

CN115895210BActive Publication Date: 2025-04-01KINGFA SCI & TECH CO LTD +1
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202211507125.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-11-29
Publication Date
2025-04-01
Estimated Expiration
2042-11-29

AI Technical Summary

Technical Problem

When existing biodegradable materials are used in membrane bags, consumers generally report that the odor is heavy, which has hindered the promotion and use of biodegradable materials, especially in areas such as catering bags.

Method used

Using a biodegradable material that is resistant to aging and low VOC and low odor, including polyhexadic acid butylene terephthalate, polylactic acid, inorganic fillers, adsorbents and additives, mixing and extrusion granulation through high blending and shear blending, and vacuum extraction and extraction agents are used in the process to reduce odor and VOC.

Benefits of technology

It effectively reduces the odor and VOC of the material, improves the aging resistance of the material, and expands the application range of biodegradable materials in the field of plastic bags.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0003969527100000061
    Figure BDA0003969527100000061
  • Figure BDA0003969527100000071
    Figure BDA0003969527100000071
  • Figure BDA0003969527100000091
    Figure BDA0003969527100000091
Patent Text Reader

Abstract

The present invention discloses an aging-resistant low-VOC low-odor biodegradable material and its preparation method and application, and relates to the field of polymer materials. It includes polybutylene adipate terephthalate, polylactic acid, an adsorbent, an inorganic filler and an auxiliary agent; the adsorbent is a porous structure material, the acid value of polybutylene adipate terephthalate is 10-30mol / t, the average particle size D50 of the inorganic filler is ≤5um, and the acid value of polylactic acid is ≤30mol / t. The present application utilizes an adsorbent to adsorb small organic molecules, combines the acid value of PBAT and PLA and the material and particle size of the inorganic filler, reduces the odor and VOC of the product, improves the aging resistance of the material, and has a wide range of applicability. It can be used for supermarket shopping bags, milk tea bags, take-out packaging bags, etc. It is easy to process and can greatly improve the VOC emission and odor of biodegradable film bags.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of polymer materials, and in particular to an aging-resistant, low-VOC, low-odor biodegradable material and a preparation method and application thereof. Background Art

[0002] With the threat of white pollution to the environment, the world has begun to enter a wave of plastic bans, among which the first field is the film bag field. Currently, biodegradable materials are gradually replacing non-degradable traditional plastics such as PE and PP on a global scale. However, when polybutylene adipate terephthalate (PBAT) / polylactic acid (PLA) composite materials are used in film bags, consumers generally report that the odor is heavier than that of traditional PE bags, which has caused certain obstacles to the promotion and use of biodegradable materials, especially in catering bags, such as catering takeaway bags, beverage bags and other fields, which seriously restricts the expansion of biodegradable materials.

[0003] The current patents on the improvement of biodegradable materials of film bags generally focus on the research of degradation performance and material mechanical properties, and there is a lack of research on methods for reducing the odor of biodegradable materials. Therefore, the development of a low-VOC and low-odor biodegradable material is of great significance to the field of special materials for degradable film bags, and is an urgent problem to be solved in this field. Summary of the invention

[0004] The present invention provides an aging-resistant, low-VOC, low-odor biodegradable material and a preparation method and application thereof, so as to improve the odor of the biodegradable material, reduce VOC, improve the aging resistance, and expand the application field of the biodegradable material.

[0005] In order to solve the above technical problems, one of the purposes of the present invention is to provide an aging-resistant, low-VOC, low-odor biodegradable material, comprising the following components in parts by weight:

[0006] Polybutylene adipate terephthalate: 51 parts to 82 parts;

[0007] Polylactic acid: 2-15 parts;

[0008] Inorganic filler: 5-25 parts;

[0009] Adsorbent: 1-4 parts;

[0010] Additives: 0.1-0.55 parts;

[0011] Among them, the adsorbent is a porous structure material, the acid value of polybutylene adipate terephthalate is 10-30 mol / t, the average particle size D50 of the inorganic filler is ≤5um, and the inorganic filler is one or more of calcium carbonate, talc, and montmorillonite; the acid value of the polylactic acid is ≤30 mol / t.

[0012] By adopting the above scheme, the specific surface area of ​​the porous structure material is large. According to the interface action mechanism, the porous material with a large specific surface area is easy to adsorb small molecules. The adsorbent can adsorb the small molecules in the system under high mixing and shear blending conditions until a state of equilibrium is reached, thereby achieving the effect of reducing odor and VOC; if the inorganic filler with a larger particle size has a large friction force on the contact surface with the resin during blending, it is more likely to cause thermal decomposition and degradation of the system, thereby generating more small molecules. The present application selects inorganic fillers that have a small shear effect when blended with the resin and avoid the effect of too small a particle size affecting the dispersion effect. The friction force with the resin in the system is small, and it is not easy to cause the generation of more small molecules; in addition, the acid value range of polybutylene adipate terephthalate and polylactic acid in the present application can improve the aging resistance of the material, and combined with the material and particle size of the inorganic filler, the aging process of the resin system is delayed.

[0013] As a preferred solution, the particle size D50 of the inorganic filler is measured by a laser method, and the acid value of polybutylene adipate terephthalate and polylactic acid is measured by GB / T 264-1983 standard.

[0014] As a preferred solution, the average particle size D50 of the inorganic filler is 1-5 um.

[0015] As a preferred embodiment, the polylactic acid is one or more of PLLA, PDLA, and PLLA / PDLA copolymer.

[0016] As a preferred embodiment, the acid value of the polylactic acid is 5-20 mol / t, and the acid value of the polybutylene adipate terephthalate is 10-15 mol / t.

[0017] As a preferred embodiment, the auxiliary agent is a lubricant, and the lubricant is one or more of erucamide, oleamide, and N,N'-ethylenebisstearamide.

[0018] As a preferred embodiment, the adsorbent is one or more of activated carbon, molecular sieve, porous zeolite, porous diatomaceous earth, porous nano-silica, and porous nano-magnesium silicate.

[0019] As a preferred solution, the particle size D50 of the adsorbent is 5 μm-7 μm.

[0020] As a preferred embodiment, the inorganic filler comprises talc and calcium carbonate in a mass ratio of (1.5-4):1.

[0021] In order to solve the above technical problems, the second object of the present invention is to provide a method for preparing an aging-resistant, low-VOC, low-odor biodegradable material, comprising the following steps:

[0022] (1) adding polybutylene adipate terephthalate, polylactic acid, inorganic filler, adsorbent, and additive into a high mixing device and mixing them thoroughly for standby use to obtain a premix;

[0023] (2) The premix is ​​added into a twin-screw extruder, an extractant is added, and the premix is ​​melt-extruded into granules. During the extrusion granulation process, a mixture of VOC and the extractant is extracted by vacuum pumping, and then the mixture is baked in a drying tank to obtain a biodegradable material.

[0024] As a preferred embodiment, in step (2), the temperature of melt extrusion granulation is 130-200°C, the rotation speed is 240-380rpm, the feed rate is 400-1000kg / h, the vacuum degree is controlled at ≤-0.07MPa, the drying temperature is 60-100°C, and the drying time is 3-8 hours.

[0025] As a preferred embodiment, in step (2), the twin-screw extruder is a 65, 75A or 75D twin-screw extruder.

[0026] As a preferred embodiment, in step (2), the temperature of the melt extrusion granulation is 130-170°C.

[0027] By adopting the above scheme, the lower extrusion temperature will effectively reduce the small molecule VOC or odorous small molecules that occur when heated.

[0028] As a preferred embodiment, in step (2), the rotation speed of the twin-screw extruder is 240-340 rpm, the feed rate is 400-800 kg / h, and the vacuum degree is controlled at ≤-0.08 MPa.

[0029] By adopting the above scheme, when blending in the twin-screw extruder, small molecules, such as polar molecules such as alcohols, benzene, and aldehydes, will be emitted from the system under high mixing and shear blending conditions. The low rotation speed reduces shear damage and chain decomposition and degradation caused by shear heating, thereby reducing the generation of VOCs and odorous small molecules. A sufficiently strong vacuum will help to extract the small molecules generated by the twin-screw shear heating. In addition, the extractant extracts the small molecules, and the vacuum can extract the mixture of the extractant and the small molecules together, further enhancing the extraction effect.

[0030] As a preferred solution, the drying temperature is 70-85°C and the drying time is 4-6 hours.

[0031] By adopting the above scheme, drying can effectively accelerate the volatilization of small molecules remaining in the particles, further remove the small molecules, and reduce odor and VOC.

[0032] As a preferred embodiment, the extractant is one or more of water, methanol, ethanol, methanol-water solution, and ethanol-water solution.

[0033] By adopting the above scheme and using a polar extractant, according to the principle of like dissolves like, the emitted polar small molecules are easily soluble in the extractant. After the extractant is vaporized, it is then extracted by vacuum extraction to extract the mixture of the emitted VOCs and the extractant together, thereby achieving the effect of reducing the small molecules in the system.

[0034] In order to solve the above technical problems, the third purpose of the present invention provides an application of a low-VOC, low-odor biodegradable material in the field of plastic bags, such as supermarket shopping bags, milk tea bags, take-out packaging bags, etc.

[0035] Compared with the prior art, the embodiments of the present invention have the following beneficial effects:

[0036] 1. The adsorbent of the present application is a porous structure with a large specific surface area, so that its own porous structure has an adsorption effect, which adsorbs small molecules in the system until a state of equilibrium is reached. The product has low odor and low VOC.

[0037] 2. If the inorganic filler has a large friction force on the contact surface with the resin during blending, it is more likely to cause thermal decomposition and degradation of the system, thereby producing more small molecules. This application selects inorganic fillers with smaller friction force with the resin in the system, and inorganic fillers of a specific size are not likely to cause the production of more small molecules, further reducing odor and VOC.

[0038] 3. The acid value range of polybutylene adipate terephthalate and polylactic acid in the present application can improve the aging resistance of the material, and combined with the material and particle size of the inorganic filler, the aging process of the resin system can be delayed. DETAILED DESCRIPTION

[0039] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0040] The following Table 1 shows the sources of raw materials in the examples and comparative examples of the present application. Unless otherwise specified, adsorbents, extractants, lubricants, calcium carbonate, talc, barium sulfate, mica, and natural fibers are all commercially available, and the same adsorbents, extractants, lubricants, calcium carbonate, talc, barium sulfate, mica, and natural fibers are used in parallel experiments.

[0041] Table 1 - Sources and performance parameters of raw materials in the examples and comparative examples of the present application

[0042] Raw material name model factory Performance parameters PBAT-1 A400MF Kingfa Technology Co., Ltd. Acid value is 12mol / t PBAT-2 KHB21AP11 Hengli Acid value 28mol / t PBAT-3 MGJH-901 Mogao Acid value 35mol / t PBAT-4 —— self made Acid value 5mol / t PDLA copolymer-1 FY804 Anhui Fengyuan Acid value 14.5mol / t PDLA Copolymer-2 D070 Prak Acid value 23mol / t PDLA Copolymer-3 - self made Acid value 35mol / t Calcium carbonate-1 - Commercially available Particle size D50 = 2um Calcium carbonate-2 - Commercially available Particle size D50 = 0.5um Calcium carbonate-3 - Commercially available Particle size D50 = 15um Montmorillonite - Commercially available Particle size D50 = 2um talcum powder - Commercially available Particle size D50 = 2um Barium sulfate - Commercially available Particle size D50 = 2um Mica - Commercially available Particle size D50 = 2um

[0043] The preparation method of the polylactic acid PDLA copolymer-3 in Table 1 above comprises the following steps: dissolving 2 kg of lactide in 4 kg of hexanediol, adding 0.05% of the total raw material weight of stannous octoate, and carrying out ring-opening polymerization, first at a reaction temperature of 150 ° C. and a reaction pressure of 1000 Pa for 2 hours, and then at a reaction temperature of 170 ° C. and a reaction pressure of 500 Pa for 3 hours to obtain a polymer solid; dissolving the polymer solid in 5 wt% chloroform by refluxing, filtering the solution, and precipitating with ethanol, the volume ratio of ethanol to chloroform is 2: 1, and a white flocculent precipitate is obtained as the product, and the acid value tested is 35 mol / t.

[0044] The preparation method of polybutylene adipate terephthalate PBAT-4 in Table 1 above comprises the following steps: esterifying 1,4-butanediol and terephthalic acid at 250° C. for 5 hours, adding adipic acid and carrying out esterification reaction at 250° C. for 5 hours, and then adding (the total raw material weight accounts for 0.05%) catalyst and carrying out polycondensation reaction at 250° C. for 5 hours to obtain; wherein, the molar ratio of 1,4-butanediol to the total acid is 1.3:1, the weight ratio of terephthalic acid to the total acid is 50%, and the weight ratio of adipic acid to the total acid is 50%.

[0045] Examples 1-13

[0046] An aging-resistant, low-VOC, low-odor biodegradable material, as shown in Table 2, includes polybutylene adipate terephthalate (PBAT), polylactic acid, an inorganic filler, an adsorbent, and a lubricant, wherein the polylactic acid is a PDLA copolymer; the inorganic filler is montmorillonite, calcium carbonate or talc; the adsorbent is a molecular sieve, porous nano-silica, porous diatomaceous earth or porous nano-magnesium silicate; the particle size D50 of the adsorbent is 5-7 μm; and the lubricant is erucamide.

[0047] Table 2 - Components and contents in Examples 1-13

[0048]

[0049]

[0050] The method for preparing an aging-resistant, low-VOC, low-odor biodegradable material in the above-mentioned embodiments 1-13 comprises the following steps:

[0051] (1) adding polybutylene adipate terephthalate, polylactic acid, inorganic filler, adsorbent, and lubricant to a high mixing device and mixing them thoroughly for standby use to obtain a premix;

[0052] (2) adding the premix to a twin-screw extruder, adding an extractant, the extractant being a 50% methanol aqueous solution, and melt extruding and granulating. During the extrusion and granulation process, a mixture of VOC and the extractant emitted is extracted by vacuum extraction. The temperature of the melt extrusion and granulation is 130-190° C., the rotation speed is 240-380 rpm, the feed is 400-1000 kg / h, and the vacuum degree is controlled at ≤-0.07 MPa. The premix is ​​then baked in a drying tank at a drying temperature of 80° C. for 6 hours to obtain a biodegradable material.

[0053] (3) The prepared material is blown into a film at a temperature of 150° C. and a film thickness of 20-60 μm to obtain a plastic film bag.

[0054] Comparative Example 1

[0055] An aging-resistant, low-VOC, low-odor biodegradable material, wherein each step and the reagents and process parameters used in each step are the same as those in Example 3, except that PBAT-1 is replaced by an equal amount of PBAT-3.

[0056] Comparative Example 2

[0057] An aging-resistant, low-VOC, low-odor biodegradable material, wherein each step and the reagents and process parameters used in each step are the same as those in Example 3, except that PDLA copolymer-1 is replaced by an equal amount of PDLA copolymer-3.

[0058] Comparative Example 3

[0059] An aging-resistant, low-VOC, low-odor biodegradable material, wherein each step and the reagents and process parameters used in each step are the same as those in Example 3, except that calcium carbonate-1 is replaced by an equal amount of calcium carbonate-3.

[0060] Comparative Example 4

[0061] An aging-resistant, low-VOC, low-odor biodegradable material, wherein each step and the reagents and process parameters used in each step are the same as those in Example 3, except that calcium carbonate-1 is replaced by an equal amount of barium sulfate.

[0062] Comparative Example 5

[0063] A low-VOC, low-odor biodegradable material, wherein each step and the reagents and process parameters used in each step are the same as those in Example 3, except that calcium carbonate-1 is replaced by an equal amount of mica.

[0064] Comparative Example 6

[0065] A low-VOC, low-odor biodegradable material, wherein each step and the reagents and process parameters used in each step are the same as those in Example 3, except that calcium carbonate-1 is replaced by an equal amount of natural fiber.

[0066] Comparative Example 7

[0067] A low-VOC, low-odor biodegradable material, wherein each step and the reagents and process parameters used in each step are the same as those in Example 3, except that the content of porous diatomaceous earth is 0.

[0068] Comparative Example 8

[0069] A low-VOC, low-odor biodegradable material, wherein each step and the reagents and process parameters used in each step are the same as those in Example 3, except that PBAT-1 is replaced by an equal amount of PBAT-4.

[0070] Performance testing

[0071] 1. Odor: The plastic film bags of Examples 1-13 and Comparative Examples 1-8 were tested according to the VW AUTO PV3900 standard. The test results are shown in Table 3.

[0072] 2. TVOC: The plastic film bags of Examples 1-13 and Comparative Examples 1-8 were tested according to the VDA277 headspace method standard. The test results are shown in Table 3.

[0073] 3. Aging resistance: According to GB / T 12000-2003, the transverse and longitudinal tear strength and dart drop impact strength are tested every week. Dart drop impact test: According to method A of GB / T 9639.1-2008, the dart drop impact test is carried out, and a single film sample is used. The number of samples is not less than 20. The performance retention rate in the fourth week is calculated, and the retention rate = (initial dart drop impact-fourth week dart drop impact) / initial dart drop impact × 100%. The statistical results are shown in Table 3. The tear strength is tested according to the provisions of GB / T 16578.2-2009. The data of the samples in the longitudinal and transverse directions are tested. The performance retention rate in the fourth week is calculated, and the retention rate = (initial tear strength-fourth week tear strength) / initial tear strength × 100%. The statistical results are shown in Table 3.

[0074] 4. Average thickness: The plastic film bags of Examples 1-13 and Comparative Examples 1-8 were tested according to GB / T 6672 standard. Film blowing was performed under the same gram weight condition for each sample. The test results are shown in Table 3.

[0075] 5. Product color: The LAB values ​​of Examples 1-13 and Comparative Examples 1-8 were tested with a colorimeter. The reddishness of the material was determined based on the a value, where 0 is the median value, negative numbers are greenish, and positive numbers are reddish.

[0076] Table 3 - Performance test results of Examples 1-13 and Comparative Examples 1-8

[0077]

[0078]

[0079] Combining the performance test results of Examples 3, 11-12 and Comparative Examples 1-2 in Table 3, it can be seen that the higher the resin acid value, that is, the more the content of terminal carboxyl COOH, the carboxyl group on the end will accelerate the breakage of the PBAT molecular chain, resulting in poor aging performance. The acid value range of polybutylene adipate terephthalate and polylactic acid in the present application can improve the aging resistance of the material. Combined with the material of the inorganic filler, the aging process of the resin system is delayed. The color value A of the final biodegradable material is below 1.4, the TVOC value is below 6.9 (10 μg / C / g), the average thickness is below 22.2 μm, the odor level reaches below 4, the fourth week of the wet heat aging test, the drop impact retention rate is above 30%, and the fourth week of the wet heat aging test. The longitudinal and transverse retention rates of the tear strength are both above 60%.

[0080] Combining the performance test results of Example 3 and Comparative Example 3 in Table 3, it can be seen that when the particle size of the inorganic filler is larger, the aging resistance, odor and VOC of the material are significantly reduced. Since the particle size of the filler is larger and the powder is coarser, more odor small molecules are generated by friction during the high-mixing process of melting.

[0081] Combining the performance test results of Example 3 and Comparative Examples 3-6 in Table 3, it can be seen that the material and particle size of the inorganic filler have a certain influence on the odor and aging resistance of the product. The particle size of the filler is larger and the powder is coarser. During the high-mixing process of melting, more odor small molecules are generated by friction, and the film thickness of the material will also be affected and reduced, resulting in the film becoming less dense and the film thickness will increase, thereby reducing the tensile strength. The present application selects inorganic fillers with smaller particle sizes, and the materials of the inorganic fillers are selected from calcium carbonate, talc and montmorillonite, which can ensure that the odor is reduced while improving the aging resistance.

[0082] Combining the performance test results of Example 3 and Comparative Example 8 in Table 3, it can be seen that the acid value of PBAT is too low, resulting in discoloration of the final material. Compared with the A value of Example 3, the positive value of the A value in Comparative Example 9 is too high at 2, indicating that the material is reddish, which limits the application field of the product.

[0083] Combining the performance test results of Examples 3 and 6-9 in Table 3, it can be seen that the inorganic filler is a compound of talcum powder and calcium carbonate, which can further improve the aging resistance of the material while ensuring the reduction of odor, and has good comprehensive performance.

[0084] The specific embodiments described above further illustrate the purpose, technical solutions and beneficial effects of the present invention. It should be understood that the above description is only a specific embodiment of the present invention and is not intended to limit the scope of protection of the present invention. It is particularly pointed out that for those skilled in the art, any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention should be included in the scope of protection of the present invention.

Claims

1. An aging-resistant, low-VOC, low-odor biodegradable material, characterized in that: It comprises the following components in parts by weight: Polybutylene adipate terephthalate: 51 parts to 82 parts; Polylactic acid: 2-15 parts; Inorganic filler: 5-25 parts; Adsorbent: 1-4 parts; Additives: 0.1-0.55 parts; Among them, the adsorbent is a porous structure material, the average particle size D50 of the inorganic filler is ≤5um, and the inorganic filler includes talcum powder and calcium carbonate in a mass ratio of (1.5-4):1; the acid value of the polylactic acid is 5-20 mol / t, and the acid value of the polybutylene adipate terephthalate is 10-15 mol / t.

2. The aging-resistant, low-VOC, low-odor biodegradable material according to claim 1, characterized in that: The polylactic acid is one or more of PLLA, PDLA, and PLLA / PDLA copolymer.

3. The aging-resistant, low-VOC, low-odor biodegradable material according to claim 1, characterized in that: The auxiliary agent is a lubricant, and the lubricant is one or more of erucamide, oleamide, and N,N'-ethylenebisstearamide.

4. The aging-resistant, low-VOC, low-odor biodegradable material according to claim 1, characterized in that: The adsorbent is one or more of activated carbon, molecular sieve, porous zeolite, porous diatomaceous earth, porous nano-silicon dioxide, and porous nano-magnesium silicate. The particle size D50 of the adsorbent is 5 μm-7 μm.

5. A method for preparing an aging-resistant, low-VOC, low-odor biodegradable material as claimed in any one of claims 1 to 4, characterized in that: The following steps are involved: (1) adding polybutylene adipate terephthalate, polylactic acid, inorganic filler, adsorbent, and additive into a high mixing device and mixing them thoroughly for standby use to obtain a premix; (2) The premix is ​​added into a twin-screw extruder, an extractant is added, and the premix is ​​melt-extruded into granules. During the extrusion granulation process, a mixture of VOC and the extractant is extracted by vacuum pumping, and then the mixture is baked in a drying tank to obtain a biodegradable material.

6. The method for preparing an aging-resistant, low-VOC, low-odor biodegradable material according to claim 5, characterized in that: In step (2), the extractant is one or more of water, methanol, ethanol, methanol-water solution, and ethanol-water solution.

7. The method for preparing an aging-resistant, low-VOC, low-odor biodegradable material according to claim 5, characterized in that: In step (2), the temperature of melt extrusion granulation is 130-200°C, the rotation speed is 240-380rpm, the feed rate is 400-1000kg / h, the vacuum degree is controlled at ≤-0.07MPa, the drying temperature is 60-100°C, and the drying time is 3-8 hours.

8. Use of the aging-resistant, low-VOC, low-odor biodegradable material according to any one of claims 1 to 4 in the field of plastic bags.

Citation Information

Patent Citations

  • Biodegradable material and preparation method and use thereof

    CN105273377A

  • Low-odor sterilization reinforced ABS (acrylonitrile butadiene styrene) automobile rearview mirror frame material and method for preparing same

    CN107915948A

  • Low-odor low-emission polypropylene composite material and preparation method thereof

    CN108250562A

  • Biodegradable agricultural film with weeding effect and preparation method of biodegradable agricultural film

    CN109762308A

  • Low-odor composite material produced by utilizing waste plastics and production method thereof

    CN111171428A